2019
DOI: 10.1037/ser0000257
|View full text |Cite
|
Sign up to set email alerts
|

Development and pilot study of a suicide prevention intervention delivered by peer support specialists.

Abstract: Suicide rates in the United States have been increasing in recent years, and the period after an inpatient psychiatric hospitalization is one of especially high risk for death by suicide. Peer support specialists may play an important role in addressing recommendations that suicide prevention activities focus on protective factors by improving hope and connectedness. The present study developed a peer specialist intervention titled Peers for Valued Living (PREVAIL) to reduce suicide risk, incorporating compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(84 citation statements)
references
References 55 publications
2
76
0
Order By: Relevance
“…The recent PREVAIL US pilot study that examined the role of peer support for people who are suicidal showed that peers can instill hope to allow people to know that recovery is possible. All peer support workers who took part in this pilot received training in motivational interviewing, how to listen, how to advise, and how to provide psychosocial support, and the intervention was feasible, acceptable to patients, and effective with a recommendation that there should be fidelity to the peer training program (Pfeiffer, King, Ilgen, et al, ).…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…The recent PREVAIL US pilot study that examined the role of peer support for people who are suicidal showed that peers can instill hope to allow people to know that recovery is possible. All peer support workers who took part in this pilot received training in motivational interviewing, how to listen, how to advise, and how to provide psychosocial support, and the intervention was feasible, acceptable to patients, and effective with a recommendation that there should be fidelity to the peer training program (Pfeiffer, King, Ilgen, et al, ).…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…These described seven programs that were from four different countries: USA (3), Germany (2), China (1), and Australia (1), and which varied in setting and design (see Table 1). Of the seven programs, four included an evaluation component (23)(24)(25)(26)(27) and three provided descriptive accounts of a program (28)(29)(30). Four peer support programs provided group support (23)(24)(25)(26)29), two were designed to deliver one-on-one support (27,28) and one program included mixed modes of support (30).…”
Section: Types Of Suicide Prevention Peer Support Programsmentioning
confidence: 99%
“…Of the seven programs, four included an evaluation component (23)(24)(25)(26)(27) and three provided descriptive accounts of a program (28)(29)(30). Four peer support programs provided group support (23)(24)(25)(26)29), two were designed to deliver one-on-one support (27,28) and one program included mixed modes of support (30). Regarding the program settings, two programs were delivered in clinical settings (27,30), two in the community (23,28), two online (24)(25)(26) and one in schools (29).…”
Section: Types Of Suicide Prevention Peer Support Programsmentioning
confidence: 99%
See 2 more Smart Citations